2018
DOI: 10.1177/0142331218764566
|View full text |Cite
|
Sign up to set email alerts
|

Quantum neural network-based intelligent controller design for CSTR using modified particle swarm optimization algorithm

Abstract: In this paper, a combination of a multi-layer quantum neural network (QNN) with the particle swarm optimization (PSO) algorithm is used with the aim of controlling a continuous stirred-tank reactor (CSTR) system. The CSTR process is highly non-linear and its dynamics are significantly sensitive to system parameter values. Normally, conventional controllers with fixed coefficients are applied to control this kind of system. In highly non-linear systems, having fixed controller coefficients in different operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…By relying on the uncertainty and polymorphism of quantum, the particle can obtain any position with different probabilities, and guide the particle to explore the global optimal position more efficiently. Good results have been achieved in parameter optimization (30)(31).…”
Section: Qpso Algorithm and Its Parameter Selection Processmentioning
confidence: 94%
“…By relying on the uncertainty and polymorphism of quantum, the particle can obtain any position with different probabilities, and guide the particle to explore the global optimal position more efficiently. Good results have been achieved in parameter optimization (30)(31).…”
Section: Qpso Algorithm and Its Parameter Selection Processmentioning
confidence: 94%
“…An initial study trained them using PSO and reported superior performance in PID control scheme. [ 259 ]…”
Section: Miscellaneous Ai‐based Process Control Technologiesmentioning
confidence: 99%
“…In which x = sin ( t∕10) . In order to have a quantitative comparison, consider the criterion Fitness = ∫ 10 0 � ∑ i e 2 i � dt [43][44][45][46][47][48][49][50][51][52]. All the controller parameters are the same as those presented in simulation 1.…”
Section: Simulation 2: Comparison Between Different Uncertainty Estimmentioning
confidence: 99%